Effect of Electrode Distance, Stirring Speed and Contact Time on Removal of Polyethylene Microplastics (Microbeads) Using Electrocoagulation Method - Fadhila Fadhila; Zulkarnaini Zulkarnaini; Amir Husin; Ferdy Ashari Syawal (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Abstract: Daily use of personal care products containing microbeads causes severe problems for the aquatic environment. Greywater is a pathway for microbeads to enter domestic waste and wastewater treatment plants (WWTPs) from personal care products. Their tiny size and hydrophobic nature allow microbeads to escape from WWTPs and end up in surface water. Therefore, processing efforts are needed to remove microbeads, one of which is using the electrocoagulation method with aluminum (Al) electrodes. This study aims to evaluate the performance of the electrocoagulation process using Al electrodes arranged in a monopolar configuration in a batch reactor to see the effect of variations in distance between electrodes of 1, 2.5, and 3.5 cm, stirring speed of 150, 200, and 250 rpm; with the contact time 60, 120, and 180 minutes in removing microbeads from artificial wastewater. This research shows that the best efficiency value of 99.30% occurs in operating conditions with a distance between electrodes of 2.5 cm, a stirring speed of 150 rpm, and a contact time of 180 minutes. ANOVA results showed that distance between electrodes, stirring speed, and contact time significantly affected microbead removal efficiency (p<0.05). The results of this research can be a reference for alternative tertiary processing at WWTPs.Abstrak: Penggunaan produk perawatan pribadi sehari-hari yang mengandung microbeads menyebabkan masalah serius bagi lingkungan perairan. Greywater merupakan jalur masuknya microbeads ke dalam limbah domestik dan instalasi pengolahan air limbah (IPAL) dari produk perawatan pribadi. Ukurannya yang sangat kecil dan sifat hidrofobiknya memungkinkan microbeads keluar dari IPAL dan berakhir ke air permukaan. Oleh karena itu diperlukan upaya pengolahan untuk menyisihkan microbeads, salah satunya dengan menggunakan metode elektrokoagulasi dengan elektroda aluminium (Al). Penelitian ini bertujuan untuk mengevaluasi kinerja proses elektrokoagulasi menggunakan elektroda Al yang disusun dalam konfigurasi monopolar dalam reaktor batch untuk melihat pengaruh variasi jarak antar elektroda 1, 2,5, dan 3,5 cm, kecepatan pengadukan 150, 200, dan 250 rpm, dan waktu kontak 60, 120, dan 180 menit dalam menyisihkan microbeads dari air limbah artifisial. Penelitian ini menunjukkan bahwa nilai efisiensi terbaik sebesar 99,30% terjadi pada kondisi operasi dengan jarak antar elektroda 2,5 cm, kecepatan pengadukan 150 rpm, dan waktu kontak 180 menit. Hasil ANOVA menunjukkan bahwa jarak antar elektroda, kecepatan pengadukan, dan waktu kontak berpengaruh signifikan terhadap efisiensi penyisihan microbead (p<0,05). Hasil penelitian ini dapat menjadi referensi alternatif pengolahan tersier di IPAL.